The Effect of Drill Smash Exercises on Smash Accuracy in Badminton Extraculicular Participants - Candra, Aditya Dwi; Purwoto, Septyaningrum Putri; Handayani, Heni Yuli; Himawan, Agus (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The smash is one of the most crucial shots in badminton, requiring a combination of strength, speed, and accuracy to achieve maximum effectiveness. Drilling practice has been recognized as an effective method for improving the technical skills of badminton players. This study aims to evaluate the effectiveness of smash drilling practice on smash accuracy in badminton players. This research is an experimental study involving 12 students from SMPN 3 Satu Atap Galis - Maduran - East Java - Indonesia. The smash drilling practice sessions were designed to sharpen the technical and tactical aspects of the smash through structured repetitions over a period of 6 weeks. The research results indicate that the experimental group undergoing smash drilling practice experienced a significant improvement in smash accuracy. The average pre-test score was 18.75, and the average post-test score was 23.08. The normality test yielded p-values of 0.068 for the pre-test and 0.324 for the post-test, indicating that the data follow a normal distribution at a 5% coefficient. The paired sample t-test resulted in a p-value of 0.000 with a coefficient of 0.05, indicating a significant difference. These findings indicate that drilling smash training is effective in improving badminton players' technical skills, especially in terms of smash accuracy.